2011
DOI: 10.1038/cmi.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HBsAg-specific antibodies from a mammalian cell displayed full-length human antibody library of healthy immunized donor

Abstract: Hepatitis B immunoglobulin (HBIG) is important in the management of hepatitis B virus (HBV) infection. Aiming to develop recombinant monoclonal antibodies as an alternative to HBIG, we report the successful identification of HBV surface antigen (HBsAg)-specific antibodies from a full-length human antibody library displayed on mammalian cell surface. Using total RNA of peripheral blood mononuclear cells of a natively immunized donor as template, the antibody repertoire was amplified. Combining four-way ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Site-specific integration of transgenes directed by Flp recombinase using the commercial "Flp-In" system has previously been described. 10,11 In direct comparison with the nuclease-directed system presented here, we found the Flp-In system to be deficient (see supplementary section), mirroring the rather limited success both in the original publications and subsequently by others. 12 This is likely due to the fact that the Flp-In system is designed for accurate integration in a limited number of clones rather than large library construction.…”
Section: Introductionsupporting
confidence: 59%
“…Site-specific integration of transgenes directed by Flp recombinase using the commercial "Flp-In" system has previously been described. 10,11 In direct comparison with the nuclease-directed system presented here, we found the Flp-In system to be deficient (see supplementary section), mirroring the rather limited success both in the original publications and subsequently by others. 12 This is likely due to the fact that the Flp-In system is designed for accurate integration in a limited number of clones rather than large library construction.…”
Section: Introductionsupporting
confidence: 59%
“…As shown in Figure 5, the induction of anti-HBV specific immune response in the liverdraining LNs was observed, and the adoptive transfer of cells from the liver-draining LN of HBV plasmid-injected mice into Rag1 2/2 mice can effectively decrease serum HBsAg levels in recipient mice. Although a previous study indicated that production of HBsAg-specific antibodies is important in the management of HBV infection, 25 whether the anti-HBs are produced in the liver-draining LNs needs further study. Collectively, we characterized the involvement of the liverdraining LNs in the immune response to HBV and recognized them as contributing factors to HBV elimination.…”
Section: Induction Of Anti-hbv Responses In the Liver-draining Lnsmentioning
confidence: 99%
“…As the need for therapeutic antibodies for treatment of human diseases increases, platforms will transition more towards mammalian cell display, requiring corresponding advancement in all aspects of library construction. We reported the development of a unique mammalian display platform [13] - [18] . In our platform, a trans-membrane (TM) domain was fused to the 3′end of heavy chain in frame to display full-length antibody on mammalian cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Dual expression vectors containing both heavy and light chain genes can be constructed in single four-way ligation [14] . Several full-length fully human antibody display libraries with a combinational diversity of 10 9 have been constructed [15] – [17] , and antigen-specific antibodies have been identified from one of the constructed libraries [18] .…”
Section: Introductionmentioning
confidence: 99%